2010
DOI: 10.1111/j.1365-2141.2009.08040.x
|View full text |Cite
|
Sign up to set email alerts
|

Epigallocatechin‐3‐gallate induces cell death in acute myeloid leukaemia cells and supports all‐trans retinoic acid‐induced neutrophil differentiation via death‐associated protein kinase 2

Abstract: Summary Acute promyelocytic leukaemia (APL) patients are successfully treated with all‐trans retinoic acid (ATRA). However, concurrent chemotherapy is still necessary and less toxic therapeutic approaches are needed. Earlier studies suggested that in haematopoietic neoplasms, the green tea polyphenol epigallocatechin‐3‐gallate (EGCG) induces cell death without adversely affecting healthy cells. We aimed at deciphering the molecular mechanism of EGCG‐induced cell death in acute myeloid leukaemia (AML). A signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
69
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(79 citation statements)
references
References 40 publications
10
69
0
Order By: Relevance
“…67LR has been identified as a cell surface EGCG receptor that mediates an antitumor effect of EGCG in vivo (12,13). Furthermore, 67LR is required for EGCG-induced selective killing of multiple myeloma and AML cells, whereas peripheral blood mononuclear cells (PBMC) are spared (2,3). Such findings provide a rationale for the clinical evaluation of EGCG as a 67LR-targeting drug.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…67LR has been identified as a cell surface EGCG receptor that mediates an antitumor effect of EGCG in vivo (12,13). Furthermore, 67LR is required for EGCG-induced selective killing of multiple myeloma and AML cells, whereas peripheral blood mononuclear cells (PBMC) are spared (2,3). Such findings provide a rationale for the clinical evaluation of EGCG as a 67LR-targeting drug.…”
Section: Introductionmentioning
confidence: 99%
“…The 67-kDa laminin receptor (67LR) is overexpressed in various cancers, including multiple myeloma (2), acute myeloid leukemia (AML; ref. 3), colorectal carcinoma (4), and breast carcinoma (5). Pathologic studies suggest that increased 67LR expression is correlated with lesions histologic severity and tumor progression (4).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to its identified roles in erythropoiesis 8 and granulocyte maturation, 9 in recent studies, DAPK2 has been shown to be involved in the regulation of cell death in tumors induced by therapeutic agents. It is centrally involved in the epigallocatechin-3-gallateinduced cell death in acute myeloid leukemia, 38 and it is upregulated during the resveratrol-induced cell death of cancer stem-like cells isolated from breast cancer cell lines. 39 For a better understanding of these functions, a detailed structural analysis of the different states in the DAPK2 regulatory cascade must be carried out.…”
Section: Model For Dapk2 Autophosphorylation and Activationmentioning
confidence: 99%
“…Overexpression of DAPK2 results in morphological changes reminiscent of apoptosis in adherent cells, such as membrane blebbing and condensation of nuclei (5, 6), and in reduced viability and survival in suspension cells (12,13). In line with these findings, restoration of DAPK2 activity through fusion of a constitutively active DAPK2 to CD30 in Hodgkin lymphoma cells resulted in selective apoptosis in tumor cells in vitro and in prolonged survival in a Hodgkin lymphoma mouse model (14), and depletion of DAPK2 sensitizes resistant cells to TRAIL-induced killing (15).…”
mentioning
confidence: 99%